Elixir - Amore, Emay (Edgware, Middlesex, United Kingdom : Twin Rivers Limited, 2018)
"The secret of the philosophers, the elixir vitae was gifted to Anu thousands of years ago. This is an account of his tale. Elixir tells us of our ancient history, it is a tale that speaks about the many hominids that did roam this earth, and the wars that they waged against each other.Read as Anu conquers his enemy, delves into the meaning of what it is to be alive, and explores the virtues and vices of man. Read and learn about the technologies that ancient man did wield and the magic that he was wise enough to discern. Elixir is an exploration of unrequited love, of man's insatiable blood lust and what it means to be alive."--amazon.
Keywords: Immortality -- Fiction; History, Ancient -- Fiction; Fantasy fiction